Participation of Chromatin-Remodeling Proteins in the Repair of Ultraviolet-B-Damaged DNA - Campi, Mabel (2012)
The genome of plants is organized into chromatin, affecting the rates of transcription, DNA recombination, and repair. In this work, we have investigated the consequences of reduced expression of some chromatin-remodeling factors and histone acetylation in maize (Zea mays) and Arabidopsis (Arabidopsis thaliana) in their participation in DNA repair after ultraviolet (UV)-B irradiation. Plants deficient in NFC102/NFC4 or SDG102/SDG26 showed more damaged DNA than wild-type plants; however, the Arabidopsis chc1 mutant showed similar accumulation of cyclobutane pyrimidine dimers as wild-type plants, in contrast to the increased DNA damage measured in the maize chc101 RNA interference line. In Arabidopsis, plants deficient in chromatin remodeling are also affected in the accumulation of pigments by UV-B. Plants treated with an inhibitor of histone acetyltransferases, curcumin, previous to the UV-B treatment show deficiencies in DNA repair; in addition, the chromatin remodeling-deficient plants have altered levels of acetylated histones after the UV-B treatment, demonstrating that histone acetylation is important during DNA repair in these two plant species. Arabidopsis mutants ham1 and ham2 also showed increased DNA damage after UV-B, suggesting that the role of these proteins in DNA damage repair has been conserved through evolution. However, cyclobutane pyrimidine dimer accumulation was higher in ham1 than in ham2; suggesting that HAM1 has a major role in DNA repair after UV-B. In summary, in this work, we have demonstrated that chromatin remodeling, and histone acetylation in particular, is important during DNA repair by UV-B, demonstrating that both genetic and epigenetic effects control DNA repair in plants.